High-flame-retardant ceramic silicone rubber and preparation method thereof
By using modified expandable graphite and hydrophobically modified silica aerogel as flame retardants in silicone rubber, the problem of poor compatibility of flame retardants in the prior art is solved, and the flame retardant properties and mechanical strength of silicone rubber are significantly improved.
Patent Information
- Application Number
- CN202411960061.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the prior art, when magnesium hydroxide and aluminum hydroxide are used as flame retardants, their compatibility with the matrix material is poor, resulting in poor flame retardant effect and mechanical strength of silicone rubber.
The flame retardant properties and mechanical strength of silicon rubber are improved by using silicone rubber, low-melting glass powder, ceramic additives, and modified expandable graphite and hydrophobically modified silica aerogel as flame retardant.
The flame retardant properties and mechanical strength of silicone rubber are significantly improved, forming an effective thermal insulation barrier, preventing flame and heat from being transferred to the interior of silicone rubber, and enhancing its mechanical properties.
Smart Images

Figure BDA0005216877830000141 
Figure BDA0005216877830000171 
Figure BDA0005216877830000181
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of flame retardant silicone rubber, and more specifically, to a highly flame retardant ceramic silicone rubber and a preparation method thereof. Background Art
[0002] With the development of science and technology, new energy vehicles account for an increasingly larger proportion, but the safety of new energy vehicle battery pack materials is still a huge challenge. In order to improve its safety performance, silicone rubber can be used as the material of the battery pack. Silicone rubber itself has good thermal stability. When burning under the flame, the Si-O structure of silicone rubber is transformed into a continuous, anti-oxidation, insulating network of silica ash covering the surface, thereby effectively preventing further burning, providing a material basis for the ceramicization of the composite material, thereby greatly reducing the amount of ceramic filler added; at the same time, silicone rubber is a semi-organic and semi-inorganic material with a low heat release rate, a small total heat release, and a low fire index. Ceramic silicone rubber can be sintered into a ceramic object under the burning of the flame, thereby preventing high temperature from damaging the internal. At the same time, ceramic silicone rubber does not contain halogen elements, has low smoke, non-toxicity and corrosion resistance, and is an excellent fireproof material.
[0003] In order to improve the flame retardant properties and ceramic effect of silicone rubber, flame retardants are generally added to silicone rubber. For example, the Chinese invention patent application document with application number CN2018112662152 discloses a method for preparing flame retardant ceramic silicone rubber, which uses methyl vinyl silicone rubber as the main material and nano-magnesium hydroxide and nano-aluminum hydroxide as flame retardants. The methyl vinyl silicone rubber is first kneaded, and then a vulcanizer, modified glass powder, nano-magnesium hydroxide, nano-aluminum hydroxide, zinc borate, modified dispersant, coupling agent and plasticizer are added and mixed, molded into sheets, and cold pressed to obtain flame retardant ceramic silicone rubber.
[0004] With respect to the above-mentioned related technologies, the inventors found that although magnesium hydroxide and aluminum hydroxide are used as flame retardants, although they have the advantages of low price, non-toxicity, smokelessness, good thermal stability, etc., they have poor compatibility with the matrix material, which causes them to easily agglomerate when mixed with the matrix, thereby reducing the flame retardant effect and mechanical strength of silicone rubber. Summary of the invention
[0005] In order to improve the flame retardant effect and mechanical strength of silicone rubber, the present application provides a highly flame retardant ceramic silicone rubber and a preparation method thereof.
[0006] In a first aspect, the present application provides a highly flame retardant ceramic silicone rubber, which adopts the following technical solution:
[0007] A highly flame-retardant ceramic silicone rubber, comprising the following raw materials in parts by weight: 100 parts of silicone rubber, 10-20 parts of hydroxy silicone oil, 5-10 parts of vulcanizing agent, 20-40 parts of low-melting-point glass powder, 3-5 parts of plasticizer, 2-7 parts of coupling agent, 10-20 parts of ceramic aid, 15-25 parts of white carbon black, 10-30 parts of modified expandable graphite, and 10-20 parts of hydrophobically modified silica aerogel;
[0008] The silicone rubber comprises methyl vinyl silicone rubber and liquid silicone rubber in a mass ratio of 1:0.5;
[0009] The modified expandable graphite comprises expandable graphite, halloysite, dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide in a mass ratio of 10:1-2:0.1-0.2:0.1-0.2.
[0010] By adopting the above technical solution, silica aerogel is a porous material with a three-dimensional network structure, with extreme density, large specific surface area, high porosity and extremely low thermal conductivity. Its nanostructure and pore structure give it a vacuum-like thermal insulation effect, which can significantly reduce the heat transfer effect. When silica aerogel is combined with silicone rubber, it can form an effective thermal insulation barrier to prevent flames and heat from being transferred to the inside of the silicone rubber, thereby improving the flame retardant performance. In addition, hydrophobically modified silica aerogel is added to silicone rubber as a reinforcing filler to fill the gaps between silicone rubber molecular chains and form a tighter network structure. This structure can limit the movement of silicone rubber molecular chains, thereby improving its mechanical strength. The silanol (Si-OH) on the surface of hydrophobically modified silica aerogel can improve its compatibility with silicone rubber. The interaction between the silanol and the terminal hydroxyl groups in silicone rubber can enhance the interfacial interaction between silica aerogel and silicone rubber, further improving the mechanical strength of silicone rubber. After hydrophobic modification, its good dispersion and compatibility in silicone rubber are ensured, the reinforcing effect of silica aerogel is fully exerted, and the dispersion of silica aerogel in silicone rubber is improved, thereby more effectively improving its mechanical strength.
[0011] Dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide make expandable graphite and halloysite evenly dispersed in silicone rubber. The layer structure of expandable graphite and halloysite can form a directional filling network in silicone rubber. Expandable graphite expands rapidly when heated to form a physical barrier to block the contact of flame and heat with the substrate, thereby improving the flame retardant properties of the material. The introduction of halloysite can improve the thermal stability of silicone rubber, making it difficult to decompose at high temperatures and delaying the combustion process. Moreover, after burning, halloysite can form a dense and compact residue layer on the surface of silicone rubber. This residue has a good thermal barrier effect and can further prevent the spread of flames and the transfer of heat. In addition to flame retardant properties, halloysite and expandable graphite can also play a reinforcing role in ceramic silicone rubber, thereby improving its tensile strength, elongation at break and other mechanical properties.
[0012] Optionally, the preparation method of the modified expandable graphite is as follows:
[0013] The halloysite is treated with an acid solution, washed to neutrality, and dried to obtain acid-treated halloysite;
[0014] The cellulose nanospheres are added to distilled water to prepare a treatment solution with a concentration of 2-3 wt %, and the acid-treated halloysite and expandable graphite are added, stirred and dispersed, and dried to obtain pretreated expanded graphite, wherein the mass ratio of the cellulose nanospheres to the halloysite is 0.5-1:1;
[0015] Add dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide into deionized water, stir and mix for 10-20 minutes, add the pretreated expanded graphite, ultrasonicate for 30-60 minutes, and dry.
[0016] By adopting the above technical solution, halloysite is a nanomaterial with a tubular structure, which is composed of 1:1 layered aluminosilicate, with an inner wall of aluminum oxide structure and positive charge, and an outer wall of silicon oxide structure and negative charge. Cellulose nanospheres are a non-toxic and harmless natural substance used as a bio-based intumescent flame retardant, which contains a large amount of hydroxyl groups. When halloysite is treated with acid, the inner cavity of the tube will be corroded first, the inner diameter of the tube will gradually increase, and the tube wall will become thinner. The hydrogen ions in the acid will react with the aluminum oxide structure on the surface of the halloysite to form Al 3+Cations such as cations remain in the inner cavity of the halloysite nanotubes, thereby increasing the positive charge on the inner cavity surface, while the surface hydroxyl groups of the cellulose nanospheres are negatively charged. The cellulose nanospheres can be combined with the surface of the acidified halloysite, and the cellulose nanospheres are used to modify the surface of the halloysite, thereby constructing a three-dimensional flame retardant system with the expanded graphite, reducing the popcorn effect of the expanded graphite when heated, and improving the flame retardant effect of the expanded graphite. Halloysite has a tubular structure, which can form a three-dimensional network structure for the carbon layer after combustion, providing support for the expanded graphite carbon layer. Cellulose nanospheres are a new type of nanocellulose with a nanometer-sized spherical morphology. Spherical nanocellulose particles have the characteristics of light weight, high strength, and high thermal stability. Their nanometer size leads to The carbonization effect is increased, and a dense carbon layer can be formed during the combustion process, thereby hindering the transfer of heat and the diffusion of oxygen, and playing a flame retardant role. The cellulose nanospheres are used as a carbon source, and the density of the expanded graphite carbon layer is improved after carbonization. Dodecyltrimethylammonium bromide is a cationic surfactant, and the positive charge on its surface can interact with the negative charge on the surface of expandable graphite, halloysite, and cellulose nanospheres through electrostatic adsorption and hydrogen bonds, and adsorb to the surface of modified halloysite, thereby reducing the hydrophilicity of the pretreated expanded graphite. Hexadecyltrimethylammonium bromide and dodecyltrimethylammonium bromide are compounded by electrostatic adsorption to obtain CS alkyl chains, which are adsorbed to the pretreated expanded graphite through hydrogen bonds, thereby improving the dispersibility and compatibility of the expanded graphite in silicone rubber.
[0017] Optionally, the cellulose nanospheres are pretreated as follows:
[0018] The cellulose nanospheres are dispersed in ethylene glycol and water, and then an aqueous solution of chloroplatinic acid is added after ultrasonic treatment for 20-30 minutes, and the mixture is stirred at 120-130°C for 2-3 hours, centrifuged, washed, and dried at 60-70°C to constant weight to obtain platinum-loaded cellulose nanospheres;
[0019] Platinum-loaded cellulose nanospheres and PNA nanofibers are mixed, added to a magnesium sulfate solution with a concentration of 2-3wt%, ultrasonically dispersed for 20-30 minutes, then ammonia water is added, reacted at 30-40°C for 2-3 hours, filtered, heated to 200-220°C and kept warm for 8-10 hours, and the mass ratio of platinum-loaded cellulose nanospheres to PAN nanofibers to magnesium sulfate solution is 1:0.2-0.4:1-1.5.
[0020] By adopting the above technical scheme, the loading of platinum reduces the initial thermal decomposition temperature and residual carbon rate of cellulose nanospheres, and platinum can also induce the breakage of Si-CH3 in silicone rubber and the coupling of free radicals at a lower temperature, forming cross-linking points to promote the cross-linking of silicone rubber. After loading platinum, the cellulose nanospheres can form a denser and higher carbon layer after combustion, and the silicone rubber can form a ceramic layer with a higher density and a higher degree of ceramicization after combustion, thereby having a better flame retardant effect; using ammonia water as a precipitant, magnesium sulfate is formed into magnesium hydroxide, which is attached to PAN nanofibers and platinum-loaded cellulose nanospheres, and the linear macromolecules of polyacrylonitrile form more ring structures through cyclization reaction, and the triple bond C≡N part is reduced to C=N double bond, thereby changing polyacrylonitrile from thermoplastic to thermosetting. Therefore, after coating with magnesium hydroxide, the temperature is increased. Heat treatment causes PAN nanofibers to undergo cyclization, hydrogenation and oxidation reactions. The cyclization reaction converts the linear PAN chain into a cyclized ladder structure. Dehydrogenation is the removal of hydrogen atoms in the molecule in the form of water. The oxidation reaction is the removal of hydrogen between PAN molecules and the generation of oxygen-containing groups to make the fiber more stable. The coating of magnesium hydroxide can improve the thermal stability of PAN nanofibers and cellulose nanospheres. PAN is a polymer and cellulose nanospheres are plant cellulose. Improving the thermal stability of the two can avoid the introduction of new combustion sources when expandable graphite is added. Therefore, adding platinum-loaded cellulose nanospheres and PAN nanofibers and coating the platinum-loaded cellulose nanospheres and PAN nanofibers with magnesium hydroxide can cause an expanded carbon layer to appear on the surface of the silicone rubber, promote the formation of a cross-linked network of silicone rubber during combustion, and improve the bending strength after porcelain formation.
[0021] Optionally, the preparation method of the hydrophobically modified silica aerogel is as follows:
[0022] A MXene nanosheet dispersion with a concentration of 5-10 mg / ml was prepared, polyethylene glycol was added, ultrasonic treatment was performed for 10-20 min, and air bubbles were removed by vacuum to prepare a spray solution;
[0023] The spraying liquid is evenly sprayed on the polyester fiber, and dried at 50-60° C. for 20-24 hours to obtain the modified polyester fiber, wherein the mass ratio of the polyester fiber to the spraying liquid is 1:0.2-0.3;
[0024] Water glass and deionized water were mixed in a mass ratio of 1:10, the pH was adjusted to 3, modified polyester fibers were added dropwise, and then ammonia water was added dropwise, and the mixture was immersed in anhydrous ethanol for 24 hours for solvent exchange, and then immersed in an isopropanol solution of perfluorochlorosilane for 20-24 hours, and dried at normal pressure to obtain hydrophobically modified silica aerogel, wherein the amount of modified polyester fibers added was 2-2.5wt% of the amount of water glass used.
[0025] By adopting the above technical scheme, the introduction of polyethylene glycol molecular chains improves the dispersibility of MXene nanosheets, so that the MXene nanosheets are embedded in the molecular chains of polyethylene glycol to form a strong force. At the same time, the oxygen-containing functional groups in the molecular chains and the abundant surface functional groups such as -OH and -F on the MXene nanosheets can generate covalent bonds such as ether bonds, produce hydrogen bonds and various chemical and physical forces such as electrostatic adsorption. Therefore, under the action of polyethylene glycol, the MXene nanosheets form a protective film on the polyester fiber. When burned, the MXene nanosheets can form a complete sheet structure and obtain a uniform brick wall structure. Therefore, when added to the silica aerogel, an interlaced overlapping structure can be formed in the silica network structure. The silica particles are tightly entangled with the fibers as the skeleton, the particle structure is uniform, and the porous network structure is obvious, so that the polyester fiber and the aerogel are effectively combined, which can effectively improve the toughness of the silica aerogel, thereby improving the mechanical strength of the silicone rubber.
[0026] Optionally, the potting aid is selected from at least one of boric acid, zinc borate, sodium borate, mica powder and kaolin.
[0027] By adopting the above technical solution, as the temperature rises, the ceramic additives continue to melt, making the contact between the fillers closer. When the temperature drops, a hard ceramic structure is formed, and the mechanical properties are improved accordingly.
[0028] Optionally, the coupling agent is selected from any one of a titanate coupling agent, a silane coupling agent or an aluminate coupling agent.
[0029] Optionally, the plasticizer is selected from any one of di-n-octyl phthalate, dibutyl phthalate or dimethyl phthalate.
[0030] Optionally, the vulcanizing agent is selected from one of dicumyl peroxide, 2,4-dichlorobenzoyl peroxide, and 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane, and preferably the vulcanizing agent is at least one of 2,4-dichlorobenzoyl peroxide.
[0031] In a second aspect, the present application provides a method for preparing highly flame-retardant ceramic silicone rubber, using the following technical solution:
[0032] A method for preparing highly flame-retardant ceramic silicone rubber comprises the following steps:
[0033] S1. Knead the silicone rubber at 70-90° C. for 3-6 min, add modified expandable graphite and hydrophobically modified silica aerogel, white carbon black and hydroxy silicone oil, and mix for 20-30 min to obtain a mixture;
[0034] S2, adding coupling agent, low melting point glass powder, ceramic aid and plasticizer to the mixture obtained in S1, and mixing for 60-120 minutes;
[0035] S3, vacuum-treating the product obtained in S2, adding a vulcanizing agent after cooling, and mixing for 10-20 minutes;
[0036] S4, subjecting the product obtained in S3 to primary vulcanization and secondary vulcanization to obtain highly flame-retardant ceramic silicone rubber.
[0037] By adopting the above technical scheme, a variety of raw materials are mixed, kneaded, vulcanized and other processes to produce ceramic silicone rubber with good flame retardancy and high porcelain strength.
[0038] Optionally, the primary vulcanization temperature is 140-180° C., the time is 20-40 min, the pressure is 10-15 MPa, and the secondary vulcanization temperature is 180° C.-200° C., and the time is 60-180 min.
[0039] In summary, this application has the following beneficial effects:
[0040] 1. Since the present application adopts raw materials such as silicone rubber, low-melting point glass powder, and ceramic additives, and utilizes modified expandable graphite and hydrophobically modified silica aerogel as flame retardants, and the modified expandable graphite is made of expandable graphite, halloysite, dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide can make the expanded graphite and halloysite uniformly dispersed in the silicone rubber, thereby forming a directional filling network, thereby achieving excellent flame retardant effect, preventing the spread of flame and heat transfer, and further improving the mechanical strength of the silicone rubber.
[0041] 2. In the present application, it is preferred to add cellulose nanospheres to the modified expandable graphite, which can further increase the density of the carbon layer formed after the expanded graphite and halloysite are burned, and improve the flame retardant effect. The cellulose nanospheres are also pretreated with chloroplatinic acid, platinum is loaded on their surface, and then mixed and heat-treated with PAN nanofibers and magnesium sulfate, which can form magnesium hydroxide on the platinum-loaded cellulose nanospheres and PAN nanofibers. After heat treatment, the PAN nanofibers undergo reactions such as cyclization, and the heat resistance stability is improved. Therefore, the pretreatment of cellulose nanospheres with platinum, PAN nanofibers, magnesium sulfate, etc. can further improve the flame retardant effect of cellulose nanospheres and avoid the introduction of new combustion sources.
[0042] 3. In the present application, it is preferred to use hydrophobically modified silica aerogel containing MXene nanosheets and polyester fibers. The MXene nanosheets are evenly dispersed under the action of polyethylene glycol and attached to the polyester fibers. Then the polyester fibers overlap each other in the silica aerogel to improve the mechanical strength of the silica aerogel, while the MXene nanosheets further improve the flame retardant effect of the polyester fibers. DETAILED DESCRIPTION
[0043] The following examples further illustrate the present application in detail.
[0044] Preparation Example 1-10 of Modified Expandable Graphite
[0045] Preparation Example 1: (1) 100 g of halloysite was added to 300 ml of concentrated hydrochloric acid, stirred at 50° C. for 1 h, cooled to room temperature, washed with deionized water until neutral, filtered, and dried at 105° C. to obtain acid-treated halloysite;
[0046] (2) 10 g of dodecyltrimethylammonium bromide and 10 g of hexadecyltrimethylammonium bromide were added to 1000 g of deionized water, and the mixture was stirred for 20 min. Acid-treated halloysite and expanded graphite were added, and the mixture was ultrasonicated for 30 min. The mixture was dried at 80° C. for 20 h.
[0047] Preparation Example 2: The difference from Preparation Example 1 is that an equal amount of deionized water is used to replace dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide.
[0048] Preparation Example 3: The difference from Preparation Example 1 is that halloysite is not added.
[0049] Preparation Example 4: (1) Add 100 g of halloysite to 300 ml of concentrated hydrochloric acid, stir at 50° C. for 1 h, cool to room temperature, wash with deionized water until neutral, filter and dry at 105° C. to obtain acid-treated halloysite;
[0050] (2) 100 g of cellulose nanospheres were added to distilled water to prepare a treatment solution with a concentration of 3 wt %, acid-treated halloysite and 1000 g of expandable graphite were added, stirred for 30 min, and dried at 80° C. to obtain pretreated expanded graphite, wherein the mass ratio of cellulose nanospheres to halloysite was 1:1; the preparation method of cellulose nanospheres was as follows: short cotton linter cardboard was cut into pieces, soaked in a sodium hydroxide solution with a concentration of 18 wt % for 24 h, washed with deionized water until neutral, and dried at 60° C. to obtain pretreated cellulose; the mass ratio of short cotton linter cardboard to sodium hydroxide solution was 1:40, the pretreated cellulose and 85 wt % phosphoric acid solution were mixed in a mass ratio of 1:50, the temperature was raised to 50° C., the mixture was stirred in a water bath for 10 h, 10 times the mass of deionized water of the mixture was added and allowed to stand, the supernatant was removed, the precipitate was centrifuged, dialyzed to neutral, and freeze-dried.
[0051] (3) 10 g of dodecyltrimethylammonium bromide and 10 g of hexadecyltrimethylammonium bromide were added to 1000 g of deionized water, and the mixture was stirred for 20 min. The pretreated expanded graphite was added, and the mixture was ultrasonicated for 30 min. The mixture was dried at 80° C. for 20 h.
[0052] Preparation Example 5: (1) Add 200 g of halloysite to 300 ml of concentrated hydrochloric acid, stir at 50° C. for 1 h, cool to room temperature, wash with deionized water until neutral, filter and dry at 105° C. to obtain acid-treated halloysite;
[0053] (2) 100 g of cellulose nanospheres were added to distilled water to prepare a treatment solution with a concentration of 2 wt%, acid-treated halloysite and 1000 g of expandable graphite were added, stirred for 30 min, and dried at 80° C. to obtain pretreated expanded graphite, wherein the mass ratio of cellulose nanospheres to halloysite was 0.5:1; the preparation method of cellulose nanospheres was as follows: short cotton linter cardboard was cut into pieces, soaked in a sodium hydroxide solution with a concentration of 18 wt% for 24 h, washed with deionized water until neutral, and dried at 60° C. to obtain pretreated cellulose; the mass ratio of short cotton linter cardboard to sodium hydroxide solution was 1:40, the pretreated cellulose and 85 wt% phosphoric acid solution were mixed in a mass ratio of 1:50, the temperature was raised to 50° C., the mixture was stirred in a water bath for 10 h, 10 times the mass of deionized water of the mixture was added and then allowed to stand, the supernatant was removed, the precipitate was centrifuged, dialyzed to neutral, and freeze-dried.
[0054] (3) 20 g of dodecyltrimethylammonium bromide and 20 g of hexadecyltrimethylammonium bromide were added to 1000 g of deionized water, stirred and mixed for 10 min, and pretreated expanded graphite was added, ultrasonicated for 60 min, and dried at 80° C. for 20 h.
[0055] Preparation Example 6: The difference from Preparation Example 4 is that the cellulose nanospheres are pretreated according to the following method:
[0056] 1g of cellulose nanospheres were dispersed in 300ml of ethylene glycol and 200ml of water, and after ultrasonication for 20min, 1ml of 0.0386mol / l chloroplatinic acid aqueous solution was added, and the mixture was stirred at 120℃ for 3h, centrifuged, washed with deionized water for 3 times, and dried at 60℃ to constant weight to obtain platinum-loaded cellulose nanospheres.
[0057] 10g of platinum-loaded cellulose nanospheres and 4g of PNA nanofibers were mixed, added to 15g of 3wt% magnesium sulfate solution, ultrasonically dispersed for 30min, then 5ml of ammonia water was added, reacted at 30°C for 3h, filtered, heated to 200°C and kept warm for 10h. The diameter of PAN nanofibers was 500nm and the length was 2μm.
[0058] Preparation Example 7: The difference from Preparation Example 4 is that the cellulose nanospheres are pretreated according to the following method:
[0059] 1g of cellulose nanospheres were dispersed in 300ml of ethylene glycol and 200ml of water, and after ultrasonication for 30min, 1ml of 0.0386mol / l chloroplatinic acid aqueous solution was added, and the mixture was stirred at 130℃ for 2h, centrifuged, washed with deionized water for 3 times, and dried at 70℃ to constant weight to obtain platinum-loaded cellulose nanospheres.
[0060] 10g of platinum-loaded cellulose nanospheres and 2g of PNA nanofibers were mixed, added to 10g of 2wt% magnesium sulfate solution, ultrasonically dispersed for 20min, then 4ml of ammonia water was added, reacted at 40°C for 2h, filtered, heated to 220°C and kept warm for 8h. The diameter of PAN nanofibers was 500nm and the length was 2μm.
[0061] Preparation Example 8: The difference from Preparation Example 6 is that no chloroplatinic acid aqueous solution is added.
[0062] Preparation Example 9: The difference from Preparation Example 6 is that no magnesium sulfate solution and ammonia water are added, and the platinum-loaded cellulose nanospheres and PAN nanofibers are mixed and kept warm at 220° C. for 8 h.
[0063] Preparation Example 10: The difference from Preparation Example 6 is that PAN nanofibers, magnesium sulfate solution and ammonia water were not added, and only 1 g of cellulose nanospheres were dispersed in 300 ml of ethylene glycol and 200 ml of water. After ultrasonication for 20 min, 1 ml of 0.0386 mol / l chloroplatinic acid aqueous solution was added, and the reaction was stirred at 120°C for 3 h. The mixture was centrifuged, washed with deionized water for 3 times, and dried at 60°C to constant weight.
[0064] Preparation Examples 11-14 of Hydrophobically Modified Silica Aerogel
[0065] Preparation Example 11: (1) 5 ml of water and 15 ml of hydrochloric acid were added to a polytetrafluoroethylene beaker in sequence, stirred, 1 g of LiF was added, and after waiting for 5 minutes, a MAX precursor was added (added in batches within 30 minutes), the beaker was covered and stirred for 24 hours, and the mixed solution was centrifuged at 4000 r / min for 5 minutes to make the pH of the final solution supernatant greater than 6, and the bottom separated precipitate was freeze-dried to obtain multi-layer MXene, and after ultrasonic vibration, single-layer MXene was obtained by centrifugal peeling; MXene nanosheets were dispersed in deionized water to prepare a MXene nanosheet dispersion with a concentration of 10 mg / ml, polyethylene glycol was added in a mass ratio of 1:1 to MXene nanosheets, ultrasonic treatment was performed for 20 minutes, and vacuum was drawn for 10 minutes to remove bubbles to obtain a spray liquid;
[0066] (2) 3 g of the spraying liquid was evenly sprayed on 10 g of polyester fiber and dried at 60° C. for 20 h to obtain modified polyester fiber with a length of 3 mm and a diameter of 20D;
[0067] (3) 50 g of water glass and deionized water were mixed in a mass ratio of 1:10, the pH was adjusted to 3 with concentrated sulfuric acid, modified polyester fiber was added dropwise, and then ammonia water was added dropwise, and the mixture was immersed in anhydrous ethanol for 24 h for solvent exchange, and then immersed in a mixed solution of 1 g of perfluorochlorosilane and 250 ml of isopropanol for 24 h, and dried at normal pressure to obtain a hydrophobically modified silica aerogel. The amount of modified polyester fiber added was 2.5 wt% of the amount of water glass used.
[0068] Preparation Example 12: (1) 5 ml of water and 15 ml of hydrochloric acid were added to a polytetrafluoroethylene beaker in sequence, stirred, 1 g of LiF was added, and after waiting for 5 minutes, a MAX precursor was added (added in batches within 30 minutes), the beaker was covered and stirred for 24 hours, and the mixed solution was centrifuged at 4000 r / min for 5 minutes to make the pH of the final solution supernatant greater than 6, and the bottom separated precipitate was freeze-dried to obtain multi-layer MXene, and after ultrasonic vibration, single-layer MXene was obtained by centrifugal peeling; MXene nanosheets were dispersed in deionized water to prepare a MXene nanosheet dispersion with a concentration of 5 mg / ml, polyethylene glycol was added in a mass ratio of 1:1 to MXene nanosheets, ultrasonic treatment was performed for 10 minutes, and vacuum was drawn for 15 minutes to remove bubbles to obtain a spray liquid;
[0069] (2) 2 g of the spraying liquid was evenly sprayed on 10 g of polyester fiber and dried at 50° C. for 24 h to obtain modified polyester fiber with a length of 3 mm and a diameter of 20D;
[0070] (3) 50 g of water glass and deionized water were mixed in a mass ratio of 1:10, the pH was adjusted to 3 with concentrated sulfuric acid, modified polyester fiber was added dropwise and then ammonia was added dropwise, and the mixture was immersed in anhydrous ethanol for 24 h for solvent exchange, and then immersed in a mixed solution of 1 g of perfluorochlorosilane and 250 ml of isopropanol for 20 h, and dried at normal pressure to obtain a hydrophobically modified silica aerogel. The amount of modified polyester fiber added was 2 wt % of the amount of water glass used.
[0071] Preparation Example 13: The difference from Preparation Example 11 is that the spraying liquid containing MXene nanosheets is not sprayed on the polyester fiber.
[0072] Preparation Example 14: The difference from Preparation Example 11 is that no modified polyester fiber is added.
[0073] Example
[0074] Example 1: A highly flame retardant ceramic silicone rubber, the raw material dosage is as shown in Table 1, wherein the silicone rubber comprises methyl vinyl silicone rubber and liquid silicone rubber in a mass ratio of 1:0.5, the methyl vinyl silicone rubber is selected from Shenzhen Anchengxing Technology, model 110-1, the liquid silicone rubber is selected from Shandong Dinghong New Materials, model 107, item number 325, the vulcanizing agent is diisopropylbenzene peroxide, the low melting point glass powder is selected from Foshan Chuangguo Chemical, model BL-55, the plasticizer is di-n-octyl phthalate, the coupling agent is silane coupling agent KH550, the ceramic forming aid is zinc borate, the modified expandable graphite is prepared by Preparation Example 1, and the hydrophobically modified silica aerogel is prepared by Preparation Example 11.
[0075] The method for preparing the above-mentioned highly flame-retardant ceramic silicone rubber comprises the following steps:
[0076] S1, kneading silicone rubber at 90° C. for 3 min, adding modified expandable graphite and hydrophobically modified silica aerogel, white carbon black and hydroxy silicone oil, and continuing to mix at 90° C. for 20 min to obtain a mixture;
[0077] S2, adding coupling agent, low melting point glass powder, ceramic aid and plasticizer to the mixture obtained in S1, and mixing at 90°C for 60 minutes;
[0078] S3, subjecting the obtained product of S2 to vacuum treatment, adding a vulcanizing agent after cooling, and kneading at 30° C. for 20 min, with a vacuum treatment temperature of 90° C., a vacuum degree of -0.06 MPa, and a vacuum treatment time of 20 min;
[0079] S4. The product obtained in S3 is subjected to primary vulcanization and secondary vulcanization to obtain highly flame-retardant ceramic silicone rubber. The primary vulcanization temperature is 180° C., the time is 20 min, and the pressure is 15 MPa. The secondary vulcanization temperature is 180° C., the pressure is 12 MPa, and the time is 180 min.
[0080] Table 1 Amount of raw materials used for high flame retardant ceramic silicone rubber in Examples 1-3
[0081]
[0082] Example 2: A highly flame retardant ceramic silicone rubber, the raw material dosage is as shown in Table 1, wherein the silicone rubber comprises methyl vinyl silicone rubber and liquid silicone rubber in a mass ratio of 1:0.5, the methyl vinyl silicone rubber is selected from Shenzhen Anchengxing Technology, model 110-1, the liquid silicone rubber is selected from Shandong Dinghong New Materials, model 107, item number 325, the vulcanizer is 2,4-dichlorobenzoyl peroxide, the low melting point glass powder is selected from Foshan Chuangguo Chemical, model BL-55, the plasticizer is dibutyl phthalate, the coupling agent is silane coupling agent KH550, the ceramic forming aid is mica powder, the modified expandable graphite is prepared by Preparation Example 1, and the hydrophobically modified silica aerogel is prepared by Preparation Example 12.
[0083] The method for preparing the above-mentioned highly flame-retardant ceramic silicone rubber comprises the following steps:
[0084] S1, kneading silicone rubber at 70° C. for 6 min, adding modified expandable graphite and hydrophobically modified silica aerogel, white carbon black and hydroxy silicone oil, and continuing to mix at 70° C. for 30 min to obtain a mixture;
[0085] S2, adding coupling agent, low melting point glass powder, ceramic aid and plasticizer to the mixture obtained in S1, and mixing at 70°C for 120 minutes;
[0086] S3, vacuum-treating the product obtained in S2, adding a vulcanizing agent after cooling, and kneading at 30° C. for 20 min, with a vacuum treatment temperature of 110° C., a vacuum degree of -0.03 MPa, and a vacuum treatment time of 30 min;
[0087] S4. The product obtained in S3 is subjected to primary vulcanization and secondary vulcanization to obtain highly flame-retardant ceramic silicone rubber. The primary vulcanization temperature is 140°C, the time is 30 minutes, and the pressure is 10 MPa. The secondary vulcanization temperature is 200°C, the pressure is 18 MPa, and the time is 60 minutes.
[0088] Example 3: A highly flame-retardant ceramic silicone rubber, which is different from Example 1 in that the amounts of raw materials used are as shown in Table 1.
[0089] Example 4: A highly flame-retardant ceramic silicone rubber, which differs from Example 1 in that the hydrophobically modified silica aerogel is prepared from Preparation Example 13.
[0090] Example 5: A highly flame-retardant ceramic silicone rubber, which differs from Example 1 in that the hydrophobically modified silica aerogel is prepared from Preparation Example 14.
[0091] Example 6: A highly flame-retardant ceramic silicone rubber, which is different from Example 1 in that the modified expandable graphite is made from Preparation Example 4.
[0092] Example 7: A highly flame-retardant ceramic silicone rubber, which is different from Example 1 in that the modified expandable graphite is made from Preparation Example 5.
[0093] Example 8: A highly flame-retardant ceramic silicone rubber, which is different from Example 6 in that the modified expandable graphite is made from Preparation Example 6.
[0094] Example 9: A highly flame-retardant ceramic silicone rubber, which is different from Example 6 in that the modified expandable graphite is made from Preparation Example 7.
[0095] Example 10: A highly flame-retardant ceramic silicone rubber, which is different from Example 9 in that the modified expandable graphite is made from Preparation Example 8.
[0096] Example 11: A highly flame-retardant ceramic silicone rubber, which is different from Example 9 in that the modified expandable graphite is made from Preparation Example 9.
[0097] Example 12: A highly flame-retardant ceramic silicone rubber, which is different from Example 9 in that the modified expandable graphite is made from Preparation Example 10.
[0098] Comparative Example
[0099] Comparative Example 1: A highly flame-retardant ceramic silicone rubber, which is different from Example 1 in that the modified expandable graphite is made from Preparation Example 2.
[0100] Comparative Example 2: A highly flame-retardant ceramic silicone rubber, which is different from Example 1 in that the modified expandable graphite is made from Preparation Example 3.
[0101] Comparative Example 3: A highly flame-retardant ceramic silicone rubber, which differs from Example 1 in that an equal amount of expandable graphite is used to replace the modified expandable graphite.
[0102] Comparative Example 4: A highly flame-retardant ceramic silicone rubber, which differs from Example 1 in that an equal amount of hydrophobically modified silica aerogel is used to replace the modified expandable graphite.
[0103] Performance testing
[0104] Ceramic silicone rubber was prepared according to the methods in the examples and comparative examples, and performance tests were performed according to the following methods. The test results are recorded in Table 2.
[0105] 1. Limiting oxygen index: The test refers to GB / T10707-2008, and the instrument is JF-3 limiting oxygen index instrument.
[0106] 2. Tensile strength and elongation at break: Tested in accordance with GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".
[0107] 3. Bending strength after ablation: The test standard is GB / T6569-2006 "Test method for bending strength of fine ceramics". The silicone rubber is made into a 80mm×10mm×3mm specimen, placed in a tubular furnace, heated to 800℃ at a rate of 10℃ / min, and kept warm for 30 minutes. The "three-point bending method" is used for testing, with a loading rate of 2mm / min and a span of 60mm.
[0108] Table 2 Performance test of highly flame retardant ceramic silicone rubber
[0109]
[0110]
[0111] It can be seen from the data in Table 2 that the ceramic silicone rubber made of the modified expandable graphite prepared in Preparation Example 1 and the hydrophobic modified silica aerogel prepared in Preparation Examples 11-12 and silicone rubber has an oxygen index higher than 28%, has an excellent flame retardant effect, and has a tensile strength greater than 6 MPa, has strong bending and stretching resistance, and has a large bending strength after being ablated into porcelain.
[0112] In Example 4, the hydrophobically modified silica aerogel prepared in Preparation Example 13 was used. Compared with Preparation Example 11, Preparation Example 13 did not spray the spray liquid containing MXene nanosheets on the polyester fiber. As can be seen from Table 2, the oxygen index of the ceramic silicone rubber prepared in Example 4 was reduced, and the bending strength after ceramic formation was reduced. It can be seen that MXene nanosheets can enhance the flame retardant effect of silica aerogel and enhance the ceramic strength.
[0113] In Example 5, the hydrophobically modified silica aerogel prepared in Preparation Example 14 was used, to which polyester fibers containing MXene nanosheets on the surface were not added. As can be seen from Table 2, the flame retardant effect of the ceramic silicone rubber was weakened, and the tensile strength and the like also decreased significantly.
[0114] Compared with Example 1, Examples 6 and 7 respectively use the modified expandable graphite prepared in Preparation Examples 4 and 5, and compared with Preparation Example 1, a certain amount of cellulose nanospheres are added. The data in Table 2 show that the ceramic silicone rubber prepared in Examples 6 and 7 has better flame retardant effect, increased oxygen index, and greater bending strength after ablation.
[0115] In Example 8 and Example 9, the modified expandable graphite prepared in Preparation Example 6 and Preparation Example 7 was used respectively. Compared with Example 6 using Preparation Example 4, the cellulose nanospheres in Example 8 and Example 9 were further treated with platinum and PAN nanofibers. It can be seen that the flame retardant effect of the ceramic silicone rubber prepared in Example 8 and Example 9 was enhanced.
[0116] In Example 10, the modified expandable graphite prepared in Preparation Example 8 was used. Compared with Preparation Example 6 in Example 9, no chloroplatinic acid aqueous solution was added, that is, no platinum was loaded on the cellulose nanospheres. It can be seen that its flame retardant effect was slightly reduced, and the bending strength was reduced after porcelain formation.
[0117] Example 11 Compared with Example 9, the modified expandable graphite prepared in Preparation Example 9 was used, wherein no magnesium sulfate solution and ammonia water were added, and platinum-loaded cellulose nanospheres were mixed with PAN nanofibers and subjected to high-temperature treatment to prepare the modified expandable graphite. It can be seen that the flame retardant effect of the ceramic silicone rubber prepared in this way is reduced.
[0118] In Example 12, the modified expandable graphite prepared in Preparation Example 10 was used. In Preparation Example 10, PAN nanofibers and magnesium sulfate were not added, and only platinum was loaded on the cellulose nanospheres. Table 2 shows that the tensile strength of the ceramic silicone rubber prepared in Example 12 decreased, and the ceramic bending strength was weakened.
[0119] In Comparative Examples 1 and 2, the modified expandable graphite prepared in Preparation Examples 2 and 3 was used respectively. In Preparation Example 2, dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide were not added, and in Preparation Example 3, halloysite was not added. It can be seen that the tensile strength of the ceramic silicone rubber prepared in Comparative Example 1 is significantly reduced, and the flame retardant performance is weakened. Although the tensile strength in Comparative Example 2 does not change much, the flame retardant effect is weakened.
[0120] In Comparative Example 3, expandable graphite is used, and in Comparative Example 2, hydrophobically modified silica aerogel is used to replace expandable graphite. The data in Table 2 show that the flame retardant effect of the ceramic silicone rubber prepared in Comparative Example 3 and Comparative Example 4 is significantly reduced, and the ceramic strength is weakened, and the mechanical properties are reduced.
[0121] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A highly flame retardant ceramic silicone rubber, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of silicone rubber, 10-20 parts of hydroxy silicone oil, 5-10 parts of vulcanizing agent, 20-40 parts of low melting point glass powder, 3-5 parts of plasticizer, 2-7 parts of coupling agent, 10-20 parts of ceramic forming aid, 15-25 parts of white carbon black, 10-30 parts of modified expandable graphite, and 10-20 parts of hydrophobically modified silica aerogel; The silicone rubber comprises methyl vinyl silicone rubber and liquid silicone rubber in a mass ratio of 1:0.5; The modified expandable graphite comprises expandable graphite, halloysite, dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide in a mass ratio of 10:1-2:0.1-0.2:0.1-0.
2.
2. The highly flame retardant ceramic silicone rubber according to claim 1, characterized in that: The preparation method of the modified expandable graphite is as follows: The halloysite is treated with an acid solution, washed to neutrality, and dried to obtain acid-treated halloysite; The cellulose nanospheres are added to distilled water to prepare a treatment solution with a concentration of 2-3 wt %, and the acid-treated halloysite and expandable graphite are added, stirred and dispersed, and dried to obtain pretreated expanded graphite, wherein the mass ratio of the cellulose nanospheres to the halloysite is 0.5-1:1; Add dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide into deionized water, stir and mix for 10-20 minutes, add the pretreated expanded graphite, ultrasonicate for 30-60 minutes, and dry.
3. The highly flame retardant ceramic silicone rubber according to claim 2, characterized in that: The cellulose nanospheres are pretreated as follows: The cellulose nanospheres are dispersed in ethylene glycol and water, and then an aqueous solution of chloroplatinic acid is added after ultrasonic treatment for 20-30 minutes, and the mixture is stirred at 120-130°C for 2-3 hours, centrifuged, washed, and dried at 60-70°C to constant weight to obtain platinum-loaded cellulose nanospheres; Platinum-loaded cellulose nanospheres and PNA nanofibers are mixed, added to a magnesium sulfate solution with a concentration of 2-3wt%, ultrasonically dispersed for 20-30 minutes, then ammonia water is added, reacted at 30-40°C for 2-3 hours, filtered, heated to 200-220°C and kept warm for 8-10 hours, and the mass ratio of platinum-loaded cellulose nanospheres to PAN nanofibers to magnesium sulfate solution is 1:0.2-0.4:1-1.
5.
4. The highly flame retardant ceramic silicone rubber according to claim 1, characterized in that: The preparation method of the hydrophobically modified silica aerogel is as follows: A MXene nanosheet dispersion with a concentration of 5-10 mg / ml was prepared, polyethylene glycol was added, ultrasonic treatment was performed for 10-20 min, and air bubbles were removed by vacuum to prepare a spray solution; The spraying liquid is evenly sprayed on the polyester fiber, and dried at 50-60° C. for 20-24 hours to obtain the modified polyester fiber, wherein the mass ratio of the polyester fiber to the spraying liquid is 1:0.2-0.3; Water glass and deionized water were mixed in a mass ratio of 1:10, the pH was adjusted to 3, modified polyester fibers were added dropwise, and then ammonia water was added dropwise, and the mixture was immersed in anhydrous ethanol for 24 hours for solvent exchange, and then immersed in an isopropanol solution of perfluorochlorosilane for 20-24 hours, and dried at normal pressure to obtain hydrophobically modified silica aerogel, wherein the amount of modified polyester fibers added was 2-2.5wt% of the amount of water glass used.
5. The highly flame retardant ceramic silicone rubber according to claim 1, characterized in that: The potting aid is selected from at least one of boric acid, zinc borate, sodium borate, mica powder and kaolin.
6. The highly flame retardant ceramic silicone rubber according to claim 1, characterized in that: The coupling agent is selected from any one of a titanate coupling agent, a silane coupling agent or an aluminate coupling agent.
7. The highly flame retardant ceramic silicone rubber according to claim 1, characterized in that: The plasticizer is selected from any one of di-n-octyl phthalate, dibutyl phthalate or dimethyl phthalate.
8. The highly flame retardant ceramic silicone rubber according to claim 1, characterized in that: The vulcanizing agent is selected from one of dicumyl peroxide, 2,4-dichlorobenzoyl peroxide and 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane, and preferably the vulcanizing agent is at least one of 2,4-dichlorobenzoyl peroxide.
9. The method for preparing the highly flame-retardant ceramic silicone rubber according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Knead the silicone rubber at 70-90° C. for 3-6 min, add modified expandable graphite and hydrophobically modified silica aerogel, white carbon black and hydroxy silicone oil, and mix for 20-30 min to obtain a mixture; S2, adding coupling agent, low melting point glass powder, ceramic aid and plasticizer to the mixture obtained in S1, and mixing for 60-120 minutes; S3, vacuum-treating the product obtained in S2, adding a vulcanizing agent after cooling, and mixing for 10-20 minutes; S4, subjecting the product obtained in S3 to primary vulcanization and secondary vulcanization to obtain highly flame-retardant ceramic silicone rubber.
10. The method for preparing highly flame-retardant ceramic silicone rubber according to claim 9, characterized in that: The primary vulcanization temperature is 140-180° C., the time is 20-40 min, the pressure is 10-15 MPa, and the secondary vulcanization temperature is 180° C.-200° C., the time is 60-180 min.
Citation Information
Patent Citations
Inorganic expandable refractory composition
CN106232555A
Low viscosity flame-retardant room temperature vulcanized foam silicone rubber and preparation method thereof
CN106589954A
Multilayer composite flame-retardant material and preparation method thereof
CN112126128A
Low-temperature ceramic silicone rubber composite material composition and preparation method thereof
CN114806180A
Flowable multi-element synergistic nano flame retardant as well as preparation method and application thereof
CN114989491A
Cited By
Nano aerogel / ceramic silicone rubber composite material, preparation method thereof and fire-resistant cable
CN120775384A
Nano-aerogel / ceramicized silicone rubber composite materials, their preparation methods, and fire-resistant cables
CN120775384B
Silica aerogel modified rubber composite material and preparation method of hose
CN121045830A
Ceramic polyphosphazene composite material for thermal insulation of power battery and preparation method of ceramic polyphosphazene composite material
CN121064639A